Leveraging on visitor's heritage tourism motivation / Khairul Azfar Adzahar, Mohd Fazil Jamaludin and Mohd Shafiz Saharan - Adzahar, Khairul Azfar; Jamaludin, Mohd Fazil; Saharan, Mohd Shafiz (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2021)
Heritage tourism is a key component in improving the tourism industry in a country and it contributes to local and national economies. It can be defined as an aspect of tourism where an individual visits historical places and sees historical treasures. With the diversity of heritage tourism resources available in Malaysia, both because of the local culture and because of colonization that took place in the past, proves that Malaysia has great potential in the heritage tourism sector. From famous and UNESCO-recognized heritage sites, the historic cities of Melaka and Georgetown to the historical places that receive less attention from tourists both within the country and abroad like significant historical sites of Lembah Bujang located in the northern part of the country; proves that the country has many and diverse heritage tourism products and has not yet been optimally exploited to increase the country's rating in the global tourism arena. However, careful study and planning must be implemented before Malaysia is able to market heritage tourism products on a large scale because it involves economic costs such as infrastructure construction costs that must be borne by the government to better facilitate heritage tourism in the country (Stynes, 1997); and it is not cheap. Among the studies that must be carried out to finalize the decision to promote the country's heritage tourism products on a large scale is to identify visitor's heritage tourism motivation. By understanding the visitor's heritage tourism motivation in depth, the country can plan appropriate heritage tourism products and plan promotional activities to historical places in Malaysia effectively. This article seeks to identify the key motivational and decision-making drivers of visitor's heritage tourism visitation choice.